(3QSGdI GdEfUGAs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3ef gGOi GdeSJLjHjf GdefJbe ef GdeTQcjf HSja ehdGfG Edg GdYGdejf HJCjjO Gdehdi Ld hYdG fWbJ hHJhajbg aJbJ hEdjg ai LejY GdCehQ s
(3BNQgG (B:s
(3bO cTaJ achfhG dPdc eSJYOjf hdeYLRGJg eSJHTQjf JchfhG hgh MSHi hKbJi hHg CSJYjf JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B25s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJhMjO hGdedd hGdfMds